PENGGUNAAN KIPAS ANGIN UNTUK MENGURANGI DISPNEA PADA PASIEN KANKER - Rani Lisa Indra (Jurnal Keperawatan Abdurrab, 2017)
Dyspnea is a subjective experience, and often found in ptients with adavnced cancer. Use of a fan is one non-pharmacological approaches in dyspnea management. Purpose of applying evidence-based nursing (EBN) was to proved the effectiveness of the use of a fan in reducing the sensation of dyspnea perceived cancer patients. EBN was applied to paatients with advanced cancer, lung cancer or cancer that has undergone metastasis to lungs that reported dyspnea. This EBN implementation demonstrated the effectiveness of the fan in reducing dyspnea sensation of cancer patients. The use of the fan is expected to be part of the management of dyspnea in cancer patients both at home and in palliative care setting.